Analysis of the Role of Zakat Collection Unit (UPZ) in Handling Poverty through the Zakat Awareness Village Program on Sebatik Island - Arizal Arizal; M. Nasir Hamzah; Sadly Abdul Djabar (Journal of Public Representative and Society Provision, 2026)
This study aims to examine the role of Zakat Collecting Units (UPZ) in addressing poverty through the implementation of the Kampung Sadar Zakat Program in Sebatik Island, Nunukan Regency. The research employed a descriptive qualitative approach through observation, in-depth interviews, and documentation. Data were analyzed using data reduction, data display, and conclusion drawing. The results show that UPZ plays a significant role in zakat collection, management, and distribution, both consumptive and productive, which contribute to improving community welfare. However, challenges remain in terms of limited resources, low zakat literacy, and geographical constraints in the border area. The study concludes that strengthening UPZ institutional capacity and government support are essential for the effectiveness of the Kampung Sadar Zakat Program in reducing poverty in Indonesia’s border regions.